Effect of dynamic capabilities in promotion Organizational Ambidexterity: analytical research at the University of Baghdad (Zien Journal of Social Sciences and Humanities, 2022)
The current research aims to test the impact of dynamic capabilities on organizational Ambidexterity at the University of Baghdad, as well as diagnosing the level of interest of the researched faculties in the research variables. The stratified included (204) represented by (deans, assistant deans, heads of departments), and the main research tool (the questionnaire) was distributed to them to survey opinions about the variables investigated, while the research used statistical programs (AMOS V.23- SPSS V.23) to analyze the primary data , with the adoption of descriptive and inferential statistics methods, to test the research hypotheses. The statistical analysis showed a number of results, the most prominent of which was a significant effect of the dynamic capabilities in their dimensions (sensing, learning, integration, coordination, reconfiguration.